Potential conflict as an opportunity for coexistence: cosmovision and attitudes of Arhuaco people towards jaguars - Pinto-Marroquin, Marianna; Castaño-Uribe, Carlos; Pérez-Torres, Jairo; Aristizabal, John F.; Santos-Fita, Dídac; Ramos Chaparro, Aquilino; Serio-Silva, Juan Carlos (Ethnobiology and Conservation, 2022)
Human responses to alterations caused by wildlife in human livelihoods depend on psychological and cultural factors, in addition to tangible factors. The ideas of transforming the discourse of conflict into a vision of coexistence, as well as of promoting a dialogue between science and ancestral knowledge, have been increasingly valued in biodiversity conservation. In ten communities of the Arhuaco people (Sierra Nevada de Santa Marta, Colombia), we qualitatively explored the role of the jaguar (Panthera onca) and its main prey (deer, peccary and paca) in the Arhuaco cosmovision, as well as how these people interpret and manage the alterations caused by these species on their livelihood from a cultural perspective. We evaluated quantitatively their cognitive, affective, and behavioral attitudes towards coexistence with these species. Our findings show that attitudes towards coexistence with the jaguar and its main prey were significantly more positive among those who have been affected by wildlife (i.e., livestock depredation and crop consumption) or who, according to their occupation (ranchers-farmers), have a higher risk of being affected. These attitudes could be better understood in light of the principles of the Arhuaco cosmovision, that have a profoundly ecological ethic, in which the jaguar plays a primordial role in the spiritual, cosmogonic, and natural order. Guaranteeing the protection of Arhuaco culture and territory could be very valuable for the conservation of the jaguar and biodiversity in the ecoregion of the Sierra Nevada de Santa Marta.